Efficacy and determinants of vacuum bell treatment in preschool children with pectus excavatum - Luo, Dengke; Cheng, Kaisheng; Yuan, Miao; Xu, Chang; He, Taozhen (Frontiers in Pediatrics, 2022)
Objective The outcome of vacuum bell (VB) treatment for preschool patients with pectus excavatum (PE) is poorly understood. We aim to investigate the short-term treatment effect of VB with a three-dimensional scanner and assess the clinical and demographic factors that might influence treatment outcomes. Methods We conducted a chart review study to review the records of preschool patients with PE who received VB treatment in a tertiary hospital from January 1, 2021, through January 1, 2022. Demographic data and chest wall deformity assessments were recorded at follow-up, including the anterior chest wall depths and depth ratio (DR). The demographic and clinical factors influencing treatment outcomes were tested using a logistic regression model. Results 139 patients who accepted vacuum bell treatment were included in the final study analysis, with a mean age of 4.6 years and a BMI of 14.9. Forty-three patients (30.9%) with a depth of less than 3 mm met the termination criteria and showed cosmetic results. The changes in depths (P < 0.001) and DR (P < 0.001) were statistically significant in 55 patients with three or four follow-ups. Multifactor logistic regression analysis showed that initial depth (OR 0.69, 95% CI 0.58–0.84, P < 0.001) and treatment period (OR 1.58, 95% CI 1.23–2.04, P < 0.001) were independent predictors of achieving complete correction. Conclusion VB is an effective treatment modality in preschool patients in the short-term follow-up, which is influenced by the depth of depression and the duration of treatment. However, further prospective studies are needed to confirm these results.